2010
DOI: 10.1590/s1516-35982010000500023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non-genetic factors on the early body weights of Tunisian local goats

Abstract: -It was evaluated in this study the environmental effects on body weights of goat kids from birth to 150 days of age of Tunisian local goat population, on the basis of 1,656 records obtained from the Arid Areas Institute of Médenine, Tunisia, during 2001-2005. Except for birth weight, individual records were adjusted for standard ages (30, 60, 90, 120 and 150 days) using either extrapolation or interpolation on field data. Data were analyzed by GLM procedure and SNK (α = 0.05) means comparison test. The kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
14
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 21 publications
17
14
2
4
Order By: Relevance
“…Hormonal differences between sexes and their resultant effects on growth may also be implicated. The difference in sex hormones, sexual dimorphism, affects feed intake, growth rate and feed efficiency (Mabrouk et al, 2010). In our study the general trend of sex variation was evident at later ages of lambs, which agrees with the findings of Hassen et al (2002) who reported the importance of sex as lambs get older in the cool highlands of Ethiopia.…”
Section: Sex Effectssupporting
confidence: 91%
“…Hormonal differences between sexes and their resultant effects on growth may also be implicated. The difference in sex hormones, sexual dimorphism, affects feed intake, growth rate and feed efficiency (Mabrouk et al, 2010). In our study the general trend of sex variation was evident at later ages of lambs, which agrees with the findings of Hassen et al (2002) who reported the importance of sex as lambs get older in the cool highlands of Ethiopia.…”
Section: Sex Effectssupporting
confidence: 91%
“…These results agree with the previous reports (Annor et al, 2012;Baneh et al, 2012;Bedhane et al, 2013) while others reported the significant effect of sex on birth weight (Mabrouk et al, 2010) and subsequent body weights (Dadi et al, 2008). The superiority of males over females may be explained by the precocity, the sexual dimorphism in favour of body growth in males than females (Mabrouk et al, 2010).…”
Section: Sex Effectssupporting
confidence: 93%
“…This may also be explained when kids stop suckling, weaning shock might contribute for further slow growth. Similar finding has been reported by Mabrouk et al (2010) who found stagnant growth of kids in heavy rain season at age of 120 or 150 days. In contrast, Annor et al (2012) reported higher body weights and faster gain of kids born during heavy and light rain seasons.…”
Section: Effects Of Season Of Birthsupporting
confidence: 91%
See 2 more Smart Citations